Comparative analysis of tobacco addiction in textbooks from 16 countries involved in the European Project BIOHEAD-CITIZEN - Dantas, Catarina (2009)
Smoking is a serious social problem that affects physical, psychological, social and economic areas. The textbook is strongly rooted in school education and works like a "screen" that links the space between the pupil and the external reality. It provides pupils with handy information, well structured and systematized contents, in order to facilitate them to build their own learning. In this context, a comparative analysis of the information conveyed by textbooks from the 16 countries involved in the European project BIOHEAD-CITIZEN was carried out. The countries differ in their geographical distribution and their historical, political and socio-cultural development: 12 European countries (Germany, Cyprus, Estonia, Finland, France, Hungary, Italy, Lithuania, Malta, Poland, Portugal and Romania), 3 African (Morocco, Mozambique and Senegal) and 1 of Near East (Lebanon). A specific part of the Health Education grid developed in the European project was used for analysing the following indicators: (i) physical effects, (ii) psychological effects, (iii) social effects, (iv) smoking prevention campaigns, and (v) environment contexts for tobacco production and consumption. Results showed that Morocco is the only country in which textbooks do not address the smoking issue. Of the 15 countries referring to this issue, only 11 countries present the three dimensions of tobacco consumption (physical, psychological and social consequences), some omit the psychological dimension, others the social one and others both. On the whole, the present study indicates that the Finnish textbook is the one which presents the smoking issue in a rather balanced way. The results show differences in political, cultural and curriculum with regard to the way textbooks of different countries explore the tobacco problematic.